A color-controllable cellulose-based structural color film and its preparation method and application

By hydrolyzing biocellulose in low concentration dilute sulfuric acid and compounding with N-PPTA and chiral glucose, a color-controllable cellulose-based structure color film was prepared, which solved the problem of poor mechanical properties of the existing film and achieved better machinery Performance and application potential.

CN116178759BActive Publication Date: 2025-02-25SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310000925.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-03
Publication Date
2025-02-25
Estimated Expiration
2043-01-03

AI Technical Summary

Technical Problem

The existing cellulose-based structure color film has poor mechanical properties and is prone to swelling when exposed to water, which limits its scale and product application.

Method used

Cellulose nanocrystals were prepared by low-concentration dilute sulfuric acid hydrolyzed biocellulose, and combined with nanopolyterephthalyl piperphenyldiamine fiber (N-PPTA) and chiral glucose to prepare color-controllable cellulose by casting method Base structure color film.

Benefits of technology

It improves the mechanical properties and color controllability of the cellulose-based structural color film, and enhances its application potential in the field of structural color anti-counterfeiting.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a color-controllable cellulose-based structural color film and its preparation method and application. The preparation method of the cellulose-based structural color film comprises the following steps: (1) adding biocellulose to dilute sulfuric acid for hydrolysis treatment, centrifuging, dialysis purification, and ultrasonic dispersion after hydrolysis to obtain a CNC suspension; (2) adding poly(p-phenylene terephthalamide) fiber and KOH to dimethyl sulfoxide, stirring the reaction, and adding water to obtain an N-PPTA solution after the reaction is completed; (3) mixing and stirring the CNC suspension, the N-PPTA solution, and the chiral glucose solution to obtain a film-forming mixed solution; (4) pouring the film-forming mixed solution into a culture dish by casting, drying, and obtaining a color-controllable cellulose-based structural color film. The method of the present invention can improve the color of the structural color film, enhance the mechanical properties, and is suitable for the field of structural color anti-counterfeiting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of structural color film functional materials, and particularly relates to a color-controllable cellulose-based structural color film and a preparation method and application thereof. Background Art

[0002] Cellulose is the most abundant and biodegradable natural polymer material in nature. It is also the earliest natural polymer material discovered and used by humans. There are highly ordered crystalline regions and irregularly arranged amorphous regions distributed inside cellulose fibers. They rely on a large number of hydrogen bonds and intermolecular forces within and between cellulose molecules to maintain the self-assembled macromolecular structure. Cellulose nanocrystals (CNCs) are generally 10 to 1000 nm in length and 5 to 30 nm in diameter. They are usually obtained by hydrolyzing cellulose raw materials with inorganic strong acids. During the hydrolysis process, the amorphous regions of cellulose are destroyed, while the crystalline regions are retained, and finally, whisker-shaped CNCs that can be stably dispersed in aqueous media to form a suspension are obtained. However, the preparation of CNCs using concentrated acid has the disadvantages of strong corrosion, high energy consumption, and a large amount of wastewater, which limits its large-scale preparation and high-value application.

[0003] CNC can self-assemble to form a cholesteric liquid crystal phase in an aqueous solution through a slow evaporation process, and the cellulose film material obtained after drying still retains this special structure and can show iridescence under natural light. The obtained color film is called a structural color film. Structural color is a physical color and is more environmentally friendly than pigments. Therefore, this type of structural color film material has broad application prospects in the fields of information security, anti-counterfeiting identification, and smart packaging. However, the structural color film formed by pure CNC has poor mechanical properties and is easy to swell in water, which is not conducive to practical applications. At present, there are no large-scale and productized application scenarios based on CNC structural color films.

[0004] Aramid fiber is a new type of high-tech synthetic fiber with the characteristics of soft texture, low density, high strength, high modulus, and high temperature resistance. It is widely used in aerospace, composite materials, ropes and cables, special protective clothing, electronic equipment and other fields. The molecular chains of poly(p-phenylene terephthalamide) fiber (PPTA) are arranged in a straight line, and it is called aramid 1414 in my country. PPTA exhibits lyotropic liquid crystal properties and is a main chain polymer liquid crystal. After chemical treatment, PPTA can obtain anisotropic liquid crystal solutions, which can be used to prepare liquid crystal materials. At present, there are no reports on its use in structural color film materials. Summary of the invention

[0005] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a color-controllable cellulose-based structural color film.

[0006] Another object of the present invention is to provide a cellulose-based structural color film with controllable color prepared by the method.

[0007] Another object of the present invention is to provide an application of the color-controllable cellulose-based structural color film.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a color-controllable cellulose-based structural color film comprises the following steps:

[0010] (1) Preparation of CNC suspension: Biocellulose is added to dilute sulfuric acid for hydrolysis, and after hydrolysis, the CNC suspension is obtained by centrifugation, dialysis purification, and ultrasonic dispersion;

[0011] (2) Preparation of N-PPTA solution: Add poly(p-phenylene terephthalamide) fiber (PPTA) and KOH into dimethyl sulfoxide (DMSO), stir to react, and add water after the reaction is completed to obtain N-PPTA (nano poly(p-phenylene terephthalamide) fiber) solution;

[0012] (3) Preparation of a film-forming mixed solution: the CNC suspension obtained in step (1), the N-PPTA solution obtained in step (2) and the glucose solution are mixed and stirred uniformly to obtain a film-forming mixed solution; wherein the glucose is at least one of levorotatory glucose (L-GLU) or dextrorotatory glucose (D-GLU);

[0013] (4) Preparation of structural color film: The film-forming mixed solution obtained in step (3) is poured into a culture dish by casting and dried to obtain a cellulose-based structural color film with controllable color.

[0014] The biocellulose described in step (1) can be obtained from conventional commercial sources or through fermentation synthesis; preferably, it is purchased from Hainan Yide Food Co., Ltd., and its liquid film thickness is 3 mm.

[0015] The concentration of the dilute sulfuric acid in step (1) is 0.20-0.40% by mass.

[0016] The mass ratio of the biocellulose to the dilute sulfuric acid solution in step (1) is (7.5-10):100.

[0017] The conditions of the acid hydrolysis treatment in step (1) are: stirring speed 220-320 rpm, reaction temperature 150-180° C., and reaction time 75-120 min.

[0018] The centrifugal conditions described in step (1) are: centrifugation at 8500-10000 rpm for 25-35 min.

[0019] The dialysis described in step (1) is performed using a dialysis bag with a molecular weight cutoff of 12000 to 14000 until the pH value of the dialysate becomes constant.

[0020] The dialysate is deionized water.

[0021] The conditions of ultrasonic dispersion described in step (1) are: 25-30° C., 250-400W ultrasonic treatment for 20-30 min.

[0022] The fiber diameter of the poly(p-phenylene terephthalamide) fiber (PPTA) described in step (2) is 600 to 1500 nm.

[0023] The mass ratio of poly(p-phenylene terephthalamide) fiber (PPTA) to KOH in step (2) is (1-3):(1-2).

[0024] The solid-liquid ratio of the total mass of the poly(p-phenylene terephthalamide) fiber (PPTA) and KOH to dimethyl sulfoxide (DMSO) described in step (2) is 1:(100-200) (g / ml).

[0025] The stirring reaction conditions in step (2) are: stirring the reaction at 600-1000 rpm for 24-48 hours.

[0026] The water described in step (2) is deionized water.

[0027] The volume ratio of water to dimethyl sulfoxide (DMSO) in step (2) is (1-2):1.

[0028] The concentration of the CNC suspension described in step (3) is 4.2-5.0% by mass.

[0029] The concentration of the N-PPTA solution described in step (3) is 0.5-0.8% by mass.

[0030] The concentration of the glucose solution in step (3) is 8.0-9.5% by mass.

[0031] The volume ratio of the CNC suspension, N-PPTA solution and glucose solution in step (3) is (8-10):1:(1-3).

[0032] The concentration of the film-forming mixed solution in step (4) is 3.0-4.5% by mass.

[0033] The thickness of the cellulose-based structural color film in step (4) is 40 to 55 μm, preferably 46 to 54 μm (i.e., a polytetrafluoroethylene round plastic culture dish with a diameter of 60 mm, and a volume of 6 to 8 ml of the film-forming mixture poured in).

[0034] The drying in step (4) is natural drying, the drying temperature is 35-40° C., and the drying time is 72-90 h (preferably 78-90 h).

[0035] A color-controllable cellulose-based structural color film is prepared by any of the methods described above.

[0036] The performance indicators of the color-controllable cellulose-based structural color film are: CNC length: 28-85nm, diameter: 25-48nm; N-PPTA length: 54-143nm, diameter: 35-58nm; film tensile strength: 118-163MPa; contact angle: 94.5-131.2°; the maximum reflection peak wavelength of the composite film to visible light: 475-648nm (from blue to red).

[0037] The color-controllable cellulose-based structural color film is used in the field of structural color anti-counterfeiting.

[0038] Compared with the prior art, the present invention has the following advantages and effects:

[0039] (1) The present invention is based on the concept of green and efficient preparation of nanocellulose. It uses low-concentration dilute sulfuric acid as a catalyst to hydrolyze biocellulose through a hydrothermal reaction to prepare cellulose nanocrystals. This not only saves production costs, but also reduces waste acid emissions. This method produces less waste acid and has certain potential in the sustainable and economical production of cellulose nanocrystals.

[0040] (2) The N-PPTA in the present invention has excellent properties such as high modulus, wear resistance and high temperature resistance. By combining N-PPTA with CNC and chiral glucose, a large number of hydrogen bonds are connected, which is beneficial to enhancing the mechanical properties of the composite film and improving the color of the structural color film. In addition, PPTA exhibits lyotropic liquid crystal properties and is an important polymer liquid crystal. The N-PPTA obtained after nano-sizing has anisotropic liquid crystal properties, which is beneficial to the formation of structural color of the composite film and can be applied to the field of structural color anti-counterfeiting.

[0041] (3) The present invention embeds left-handed (right-handed) glucose molecules in situ into the CNC liquid crystal phase self-assembly system, which can realize the molecular induction effect of chiral glucose molecules on the CNC self-assembly process and enhance the flexibility of the composite film; the chiral glucose molecules regulate the CNC self-assembly process and then realize the regulation of the structural color of the composite film. This method is simple and controllable, and has important practical significance for the large-scale preparation and industrial production of cellulose-based structural color films. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not specified in the following examples are usually in accordance with conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.

[0043] The poly(p-phenylene terephthalamide) fiber (PPTA) (fiber diameter: 600-1500 nm) used in the embodiments of the present invention was purchased from Sigma-Aldrich; the biocellulose (sheet) (liquid film thickness of 3 mm) was purchased from Hainan Yide Food Co., Ltd.; other reagents and drugs can be purchased from the market or prepared according to the existing technical methods.

[0044] The detection of various parameters involved in the embodiments of the present invention is carried out according to national standard detection methods and industry standards (repeated three times), specifically:

[0045] ①Tensile strength (GB / T 12914-2018);

[0046] ②Contact angle of water (GBT30693-2014);

[0047] ③ Test method for the maximum reflection peak wavelength of visible light of the film: A UV-visible spectrophotometer (U-4100, HITACHI) was used to test the radiation spectrum of the nanofiber-based flexible composite structure color film. The measured wavelength range was 200-800nm, the resolution was 1nm, the scanning rate was 300nm / min, the test temperature was 25°C, and the incident light was perpendicular to the film.

[0048] Example 1

[0049] This embodiment provides a method for preparing a color-controllable cellulose-based structural color film, and the specific preparation steps are as follows:

[0050] (1) Preparation of CNC: In a stainless steel autoclave, biocellulose was subjected to acid hydrolysis treatment using a 0.20% dilute sulfuric acid solution, the mass ratio of biocellulose to the dilute sulfuric acid solution was 7.5:100 (i.e., biocellulose accounted for 7.5% of the mass of the dilute sulfuric acid solution), the hydrolysis temperature was 150°C, the hydrolysis time was 75 min, the stirring speed was 220 rpm, and then centrifuged at a speed of 8500 rpm for 25 min, and then the upper suspension was taken and placed in a dialysis bag with a molecular weight cutoff of 12000-14000 and dialyzed with deionized water until the pH value of the dialysate was constant; then ultrasonic dispersion was performed at a power of 250 W and a temperature of 25°C for 20 min to finally obtain a CNC suspension;

[0051] (2) Preparation of N-PPTA: Poly(p-phenylene terephthalamide) fiber (PPTA) and KOH were added to a dimethyl sulfoxide (DMSO) reagent which was continuously stirred (600 rpm) by an electric stirrer, wherein the mass ratio of PPTA to KOH was 1:1, and the solid-liquid ratio of PPTA and KOH (PPTA+KOH) to DMSO was 1:100 (w / v, g / ml). The mixture was reacted for 24 h, and then deionized water was added to obtain a nano-poly(p-phenylene terephthalamide) fiber (N-PPTA) solution, wherein the volume ratio of deionized water to DMSO was 1:1;

[0052] (3) Preparation of a membrane-forming mixed solution: The CNC suspension (mass concentration of 4.2%) obtained in step (1) is mixed with the N-PPTA solution (mass concentration of 0.5%) and the dextran solution (mass concentration of 8.0%) prepared in step (2) in a volume ratio of 10:1:1 and stirred thoroughly;

[0053] (4) Preparation of structural color film: The film-forming mixed solution (mass concentration of 3.0%, volume of 6 ml) obtained in step (3) was poured into a polytetrafluoroethylene round plastic culture dish with a diameter of 60 mm by casting, and naturally dried at 35°C for 90 h to obtain a cellulose-based structural color film (thickness of 46 μm).

[0054] The performance indicators of the color-controllable cellulose-based structural color film of this embodiment are as follows: length of CNC: 69-85nm, diameter: 37-48nm; length of N-PPTA: 102-143nm, diameter: 47-58nm; tensile strength of the film: 118MPa; contact angle: 94.5°; maximum reflection peak wavelength of the composite film to visible light: 475nm (blue).

[0055] Example 2

[0056] This embodiment provides a method for preparing a color-controllable cellulose-based structural color film, and the specific preparation steps are as follows:

[0057] (1) Preparation of CNC: In a stainless steel autoclave, biocellulose was subjected to acid hydrolysis with a 0.30% dilute sulfuric acid solution, the mass ratio of biocellulose to the dilute sulfuric acid solution was 8.0:100, the hydrolysis temperature was 160°C, the hydrolysis time was 90 min, the stirring speed was 250 rpm, and then centrifuged at a speed of 9000 rpm for 30 min. The upper suspension was then taken and placed in a dialysis bag with a molecular weight cutoff of 12000-14000 and dialyzed with deionized water until the pH value of the dialysate was constant; then ultrasonic dispersion was performed at a power of 300 W and a temperature of 28°C for 25 min to finally obtain a CNC suspension;

[0058] (2) Preparation of N-PPTA: Poly(p-phenylene terephthalamide) fiber (PPTA) and KOH were added to a dimethyl sulfoxide (DMSO) reagent which was continuously stirred (800 rpm) by an electric stirrer, wherein the mass ratio of PPTA to KOH was 1:2, and the solid-liquid ratio of PPTA and KOH (PPTA+KOH) to DMSO was 1:200 (w / v, g / ml). The mixture was reacted for 36 h, and then deionized water was added to obtain a nano-poly(p-phenylene terephthalamide) fiber (N-PPTA) solution, wherein the volume ratio of deionized water to DMSO was 2:1;

[0059] (3) Preparation of a membrane-forming mixed solution: The CNC suspension (mass concentration of 4.5%) obtained in step (1) is mixed with the N-PPTA solution (mass concentration of 0.6%) and the dextran solution (mass concentration of 9.0%) prepared in step (2) in a volume ratio of 10:1:3 and stirred thoroughly;

[0060] (4) Preparation of structural color film: The film-forming mixed solution (mass concentration of 3.5%, volume of 7 ml) obtained in step (3) was poured into a polytetrafluoroethylene round plastic culture dish with a diameter of 60 mm by casting, and naturally dried at 37°C for 78 h to obtain a cellulose-based structural color film (thickness of 49 μm).

[0061] The performance indicators of the color-controllable cellulose-based structural color film of this embodiment are as follows: length of CNC: 54-73nm, diameter: 28-41nm; length of N-PPTA: 94-132nm, diameter: 37-50nm; tensile strength of the film: 135MPa; contact angle: 104.3°; maximum reflection peak wavelength of the composite film to visible light: 520nm (green).

[0062] Example 3

[0063] This embodiment provides a method for preparing a color-controllable cellulose-based structural color film, and the specific preparation steps are as follows:

[0064] (1) Preparation of CNC: In a stainless steel autoclave, biocellulose was subjected to acid hydrolysis with a dilute sulfuric acid solution having a mass concentration of 0.30%. The mass ratio of biocellulose to the dilute sulfuric acid solution was 9.0:100. The hydrolysis temperature was 170°C, the hydrolysis time was 105 min, and the stirring speed was 280 rpm. The mixture was then centrifuged at a speed of 9500 rpm for 35 min. The upper suspension was then taken and placed in a dialysis bag with a molecular weight cutoff of 12000 to 14000 and dialyzed with deionized water until the pH value of the dialysate was constant. The mixture was then ultrasonically dispersed at a power of 350 W and a temperature of 30°C for 25 min to obtain a CNC suspension.

[0065] (2) Preparation of N-PPTA: Poly(p-phenylene terephthalamide) fiber (PPTA) and KOH were added to a dimethyl sulfoxide (DMSO) reagent which was continuously stirred (1000 rpm) by an electric stirrer, wherein the mass ratio of PPTA to KOH was 2:1, and the solid-liquid ratio of PPTA and KOH (PPTA+KOH) to DMSO was 1:200 (w / v, g / ml). The mixture was reacted for 48 h, and then deionized water was added to obtain a nano-poly(p-phenylene terephthalamide) fiber (N-PPTA) solution, wherein the volume ratio of deionized water to DMSO was 1:1;

[0066] (3) Preparation of a membrane-forming mixed solution: The CNC suspension (mass concentration of 4.7%) obtained in step (1) is mixed with the N-PPTA solution (mass concentration of 0.7%) and the L-glucose solution (mass concentration of 9.0%) prepared in step (2) in a volume ratio of 9:1:2 and stirred thoroughly;

[0067] (4) Preparation of structural color film: The film-forming mixed solution (mass concentration of 4.0%, volume of 8 ml) obtained in step (3) was poured into a polytetrafluoroethylene round plastic culture dish with a diameter of 60 mm by casting, and naturally dried at 38°C for 85 h to obtain a cellulose-based structural color film (thickness of 51 μm).

[0068] The performance indicators of the color-controllable cellulose-based structural color film of this embodiment are as follows: length of CNC: 45-68nm, diameter: 25-38nm; length of N-PPTA: 86-108nm, diameter: 35-46nm; tensile strength of the film: 148MPa; contact angle: 119.6°; maximum reflection peak wavelength of the composite film to visible light: 603nm (yellow).

[0069] Example 4

[0070] This embodiment provides a method for preparing a color-controllable cellulose-based structural color film, and the specific preparation steps are as follows:

[0071] (1) Preparation of CNC: In a stainless steel autoclave, biocellulose was subjected to acid hydrolysis with a 0.40% dilute sulfuric acid solution. The mass ratio of biocellulose to the dilute sulfuric acid solution was 10:100. The hydrolysis temperature was 180°C, the hydrolysis time was 120 min, and the stirring speed was 320 rpm. The mixture was then centrifuged at 10,000 rpm for 35 min. The upper suspension was then placed in a dialysis bag with a molecular weight cutoff of 12,000 to 14,000 and dialyzed with deionized water until the pH value of the dialysate was constant. The mixture was then ultrasonically dispersed at a power of 400 W and a temperature of 30°C for 30 min to obtain a CNC suspension.

[0072] (2) Preparation of N-PPTA: Poly(p-phenylene terephthalamide) fiber (PPTA) and KOH were added to a dimethyl sulfoxide (DMSO) reagent which was continuously stirred (1000 rpm) by an electric stirrer, wherein the mass ratio of PPTA to KOH was 3:2, and the solid-liquid ratio of PPTA and KOH (PPTA+KOH) to DMSO was 1:200 (w / v, g / ml). After reacting for 48 h, deionized water was added to obtain a nano-poly(p-phenylene terephthalamide) fiber (N-PPTA) solution, wherein the volume ratio of deionized water to DMSO was 1:1;

[0073] (3) Preparation of a membrane-forming mixed solution: The CNC suspension (mass concentration of 5.0%) obtained in step (1) is mixed with the N-PPTA solution (mass concentration of 0.8%) and the L-glucose solution (mass concentration of 9.5%) prepared in step (2) in a volume ratio of 8:1:3 and stirred thoroughly;

[0074] (4) Preparation of structural color film: The film-forming mixed solution (mass concentration of 4.5%, volume of 8 ml) obtained in step (3) was poured into a polytetrafluoroethylene round plastic culture dish with a diameter of 60 mm by casting, and naturally dried at 40°C for 90 h to obtain a cellulose-based structural color film (thickness of 54 μm).

[0075] The performance indicators of the color-controllable cellulose-based structural color film of this embodiment are as follows: length of CNC: 28-54nm, diameter: 26-33nm; length of N-PPTA: 54-92nm, diameter: 37-45nm; tensile strength of the film: 163MPa; contact angle: 131.2°; the maximum reflection peak wavelength of the composite film to visible light: 648nm (red).

[0076] Comparative Example 1

[0077] This comparative example provides a method for preparing a cellulose-based structural color film, and the specific preparation steps are as follows:

[0078] (1) Preparation of CNC: In a stainless steel autoclave, biocellulose was subjected to acid hydrolysis treatment using a 0.20% dilute sulfuric acid solution, the mass ratio of biocellulose to the dilute sulfuric acid solution was 7.5:100, the hydrolysis temperature was 150°C, the hydrolysis time was 75 min, the stirring speed was 220 rpm, and then centrifuged at a speed of 8500 rpm for 25 min. The upper suspension was then taken and placed in a dialysis bag with a molecular weight cutoff of 12000 to 14000 and dialyzed with deionized water until the pH value of the dialysate was constant; then ultrasonic dispersion was performed at a power of 250 W and a temperature of 25°C for 20 min to finally obtain a CNC suspension;

[0079] (2) Preparation of a film-forming mixed solution: The CNC suspension (mass concentration of 4.2%) obtained in step (1) was mixed with a dextran solution (mass concentration of 8.0%) at a volume ratio of 10:1 and stirred thoroughly;

[0080] (3) Preparation of structural color film: The film-forming mixed solution (mass concentration of 3.0%, volume of 6 ml) obtained in step (2) was poured into a polytetrafluoroethylene round plastic culture dish with a diameter of 60 mm by casting, and naturally dried at 35°C for 90 h to obtain a cellulose-based structural color film (thickness of 44 μm).

[0081] The performance indicators of the cellulose-based structural color film of this embodiment are as follows: CNC length: 67-86 nm, diameter: 32-45 nm; film tensile strength: 47 MPa; contact angle: 78.3°; maximum reflection peak wavelength of the composite film to visible light: 470 nm (blue).

[0082] Comparative Example 2

[0083] This comparative example provides a method for preparing a cellulose-based structural color film, and the specific preparation steps are as follows:

[0084] (1) Preparation of CNC: In a stainless steel autoclave, biocellulose was subjected to acid hydrolysis treatment using a 0.20% dilute sulfuric acid solution, the mass ratio of biocellulose to the dilute sulfuric acid solution was 7.5:100, the hydrolysis temperature was 150°C, the hydrolysis time was 75 min, the stirring speed was 220 rpm, and then centrifuged at a speed of 8500 rpm for 25 min. The upper suspension was then taken and placed in a dialysis bag with a molecular weight cutoff of 12000 to 14000 and dialyzed with deionized water until the pH value of the dialysate was constant; then ultrasonic dispersion was performed at a power of 250 W and a temperature of 25°C for 20 min to finally obtain a CNC suspension;

[0085] (2) Preparation of N-PPTA: Poly(p-phenylene terephthalamide) fiber (PPTA) and KOH were added to a dimethyl sulfoxide (DMSO) reagent which was continuously stirred (600 rpm) by an electric stirrer, wherein the mass ratio of PPTA to KOH was 1:1, and the solid-liquid ratio of PPTA and KOH (PPTA+KOH) to DMSO was 1:100 (w / v, g / ml). The mixture was reacted for 24 h, and then deionized water was added to obtain a nano-poly(p-phenylene terephthalamide) fiber (N-PPTA) solution, wherein the volume ratio of deionized water to DMSO was 1:1;

[0086] (3) Preparation of a film-forming mixed solution: The CNC suspension (mass concentration of 4.2%) obtained in step (1) and the N-PPTA solution (mass concentration of 0.5%) prepared in step (2) were mixed in a volume ratio of 10:1 and stirred thoroughly;

[0087] (4) Preparation of structural color film: The film-forming mixed solution (mass concentration of 3.0%, volume of 6 ml) obtained in step (3) was poured into a polytetrafluoroethylene round plastic culture dish with a diameter of 60 mm by casting, and naturally dried at 35°C for 90 h to obtain a cellulose-based structural color film (thickness of 42 μm).

[0088] The performance indicators of the fiber-based structural color film of this embodiment are as follows: length of CNC: 61~83nm, diameter: 34~47nm; length of N-PPTA: 105~146nm, diameter: 43~57nm; tensile strength of the film: 93MPa; contact angle: 91.6°; the maximum reflection peak wavelength of the composite film to visible light: 488nm (blue).

[0089] Comparative Example 3

[0090] This comparative example provides a method for preparing a cellulose-based structural color film, and the specific preparation steps are as follows:

[0091] (1) Preparation of CNC: In a stainless steel autoclave, biocellulose was subjected to acid hydrolysis treatment using a 0.20% dilute sulfuric acid solution, the mass ratio of biocellulose to the dilute sulfuric acid solution was 7.5:100, the hydrolysis temperature was 150°C, the hydrolysis time was 75 min, the stirring speed was 220 rpm, and then centrifuged at a speed of 8500 rpm for 25 min. The upper suspension was then taken and placed in a dialysis bag with a molecular weight cutoff of 12000 to 14000 and dialyzed with deionized water until the pH value of the dialysate was constant; then ultrasonic dispersion was performed at a power of 250 W and a temperature of 25°C for 20 min to finally obtain a CNC suspension;

[0092] (2) Preparation of N-PPTA: Poly(p-phenylene terephthalamide) fiber (PPTA) and KOH were added to a dimethyl sulfoxide (DMSO) reagent which was continuously stirred (600 rpm) by an electric stirrer, wherein the mass ratio of PPTA to KOH was 1:1, and the solid-liquid ratio of PPTA and KOH (PPTA+KOH) to DMSO was 1:100 (w / v, g / ml). The mixture was reacted for 24 h, and then deionized water was added to obtain a nano-poly(p-phenylene terephthalamide) fiber (N-PPTA) solution, wherein the volume ratio of deionized water to DMSO was 1:1;

[0093] (3) Preparation of a membrane-forming mixed solution: The CNC suspension (mass concentration of 4.2%) obtained in step (1) is mixed with the N-PPTA solution (mass concentration of 0.5%) prepared in step (2) and the achiral glucose solution (mass concentration of 8.0%) in a volume ratio of 10:1:1 and stirred thoroughly;

[0094] (4) Preparation of structural color film: The film-forming mixed solution (mass concentration of 3.0%, volume of 6 ml) obtained in step (3) was poured into a polytetrafluoroethylene round plastic culture dish with a diameter of 60 mm by casting, and naturally dried at 35°C for 90 h to obtain a cellulose-based structural color film (thickness of 45 μm).

[0095] The performance indicators of the fiber-based structural color film of this embodiment are as follows: length of CNC: 57~82nm, diameter: 38~50nm; length of N-PPTA: 96~140nm, diameter: 41~55nm; tensile strength of the film: 98MPa; contact angle: 93.2°; the maximum reflection peak wavelength of the composite film to visible light: 497nm (blue).

[0096] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a color-controllable cellulose-based structural color film, characterized in that: The steps include: (1) Preparation of CNC suspension: Biocellulose is added to dilute sulfuric acid for hydrolysis, and after hydrolysis, the CNC suspension is obtained by centrifugation, dialysis purification, and ultrasonic dispersion; (2) Preparation of N-PPTA solution: Add poly(p-phenylene terephthalamide) fiber and KOH into dimethyl sulfoxide, stir to react, and add water after the reaction is completed to obtain N-PPTA solution; (3) Preparation of a film-forming mixed solution: the CNC suspension obtained in step (1), the N-PPTA solution obtained in step (2), and the glucose solution are mixed and stirred uniformly to obtain a film-forming mixed solution; wherein the glucose is at least one of levorotatory glucose or dextrorotatory glucose; (4) Preparation of structural color film: pouring the film-forming mixture obtained in step (3) into a culture dish by casting, and drying to obtain a cellulose-based structural color film with controllable color; The concentration of the dilute sulfuric acid in step (1) is 0.20-0.40% by mass; The mass ratio of the biocellulose to the dilute sulfuric acid solution in step (1) is 7.5 to 10:100; The mass ratio of the poly(p-phenylene terephthalamide) fiber to KOH in step (2) is 1-3:1-2; The concentration of the CNC suspension in step (3) is 4.2-5.0% by mass; The concentration of the N-PPTA solution in step (3) is 0.5-0.8% by mass; The concentration of the glucose solution in step (3) is 8.0-9.5% by mass; The volume ratio of the CNC suspension, N-PPTA solution and glucose solution in step (3) is 8-10:1:1-3.

2. The method for preparing a color-controllable cellulose-based structural color film according to claim 1, characterized in that: The concentration of the film-forming mixed solution in step (4) is 3.0-4.5% by mass; The thickness of the cellulose-based structural color film described in step (4) is 40 to 55 μm.

3. The method for preparing a color-controllable cellulose-based structural color film according to claim 1, characterized in that: The solid-liquid ratio of the total mass of the poly(p-phenylene terephthalamide) fiber and KOH to dimethyl sulfoxide in step (2) is 1 g:100-200 ml; The volume ratio of water to dimethyl sulfoxide in step (2) is 1-2:

1.

4. The method for preparing a color-controllable cellulose-based structural color film according to claim 1, characterized in that: The thickness of the biocellulose in step (1) is 3 mm; The fiber diameter of the poly(p-phenylene terephthalamide) fiber described in step (2) is 600 to 1500 nm.

5. The method for preparing a color-controllable cellulose-based structural color film according to claim 1, characterized in that: The conditions of the acid hydrolysis treatment in step (1) are: stirring speed 220-320 rpm, reaction temperature 150-180°C, reaction time 75-120 min; The dialysis described in step (1) is performed using a dialysis bag with a molecular weight cutoff of 12000 to 14000 until the pH value of the dialysate becomes constant; wherein the dialysate used for the dialysis is deionized water.

6. The method for preparing a color-controllable cellulose-based structural color film according to claim 1, characterized in that: The centrifugal conditions described in step (1) are: centrifugation at 8500-10000 rpm for 25-35 min; The conditions of ultrasonic dispersion in step (1) are: 25-30°C, 250-400W ultrasonic treatment for 20-30 min; The stirring reaction conditions in step (2) are: stirring reaction at 600-1000 rpm for 24-48 hours; The drying in step (4) is natural drying, the drying temperature is 35-40°C, and the drying time is 72-90 hours.

7. A color-controllable cellulose-based structural color film, characterized in that: It is prepared by the method according to any one of claims 1 to 6.

8. Application of the color-controllable cellulose-based structural color film according to claim 7 in the field of structural color anti-counterfeiting.

Citation Information

Patent Citations

  • Wavelength-controllable cellulose iridescent film and preparation method thereof

    CN112280072A

  • High-performance aramid fiber composite paper-based material as well as preparation method and application thereof

    CN112553946A